Syntax in action has priority over movement selection in piano playing: An ERP study - Bianco, R.; Novembre, G.; Keller, P. E.; Scharf, F.; Friederici, A. D.; Villringer, A.; Sammler, D. (Journal of Cognitive Neuroscience, 2015)
Complex human behavior is hierarchically organized. Whether or not syntax plays a role in this organization is currently under debate. The present ERP study uses piano performance to isolate syntactic operations in action planning and to demonstrate their priority over nonsyntactic levels of movement selection. Expert pianists were asked to execute chord progressions on a mute keyboard by copying the posture of a performing model hand shown in sequences of photos. We manipulated the final chord of each sequence in terms of Syntax (congruent/incongruent keys) and Manner (conventional/unconventional fingering), as well as the strength of its predictability by varying the length of the Context (five-chord/two-chord progressions). The production of syntactically incongruent compared to congruent chords showed a response delay that was larger in the long compared to the short context. This behavioral effect was accompanied by a centroparietal negativity in the long but not in the short context, suggesting that a syntax-based motor plan was prepared ahead. Conversely, the execution of the unconventional manner was not delayed as a function of Context and elicited an opposite electrophysiological pattern (a posterior positivity). The current data support the hypothesis that motor plans operate at the level of musical syntax and are incrementally translated to lower levels of movement selection.